L-Carnitine and Cholecalciferol: A Novel Approach to Amikacin Induced Nephrotoxicity - Himangshu Mahato; Vaswati Das; Supreeti Biswas (Novel Aspects on Pharmaceutical Research Vol. 7, 2023)
This chapter highlights the measurement of amikacin induced nephrotoxicity by means of abnormal renal biochemical parameters on albino rats and comparison of improvement after administration of L-carnitine & Cholecalciferol along with renal histopathology examination (HPE) of amikacin treated rats and causality assessment of amikacin induced adverse drug reactions (ADR) in hospitalized patient. Adherence to therapies is a primary determinant of treatment success. Failure to adherence is a serious problem which not only affects the patient but also the health care system. Nephrotoxicity is defining as rapid deterioration in the kidney function due to toxic effect of medications and chemicals. There are various forms, and some drugs may affect renal function in more than one way. The Study was carried out in the Department of Pharmacology in collaboration with The Department of Biochemistry, Pathology, and various clinical departments of Burdwan medical College and Hospital (BMCH). Healthy albino male rats (N=40) were taken from Institutional animal house of BMCH and were randomly divided into 4 groups. CPCSEA acclimatization guideline followed. IEAC and CREC clearances taken. Renal biochemical parameters from blood samples were analysed. Sterile water for injection was given to all group. Group I is control (only vehicle), Amikacin added to Group II, III and IV. L carnitine & Cholecalciferol was added to Group III & Group IV respectively. Post test measurement of renal biochemical parameters and HPE were done. Clinical observation of amikacin treated hospitalised patients and collection of their ADR in BMCH were done to find out correlations with animal experiment. Baseline laboratory values such as serum urea and creatinine were collected from the BHT, before and after the completion of amikacin therapy. Increased serum urea, increased serum creatinine, oliguria and swelling of face were taken as indicator of nephropathy whereas fullness in ear, tinnitus and loss of hearing were taken as indicator of ototoxicity. Statistical analyses were done using Graph Pad Prism version.4 software. Minimisation of amikacin induced nephropathy were seen, more in Group IV than Group III. HPE found the same conclusion. WHO UMC causality assessment revealed, 94.35% ADR were “probable/likely” whereas 5.65% were “possible”. The Naranjo’s adverse reaction probability scale revealed almost the same. Cholecalciferol is definitely superior to L carnitine for reducing the consequences of amikacin-induced nephropathy, according to interventional animal experiment, biochemical parameters, histology, and open label, non-interventional, prospective observational study.